SYNTHESIS OF TETRAHYDROFURAN OVER ALUMINOPHOSPHATE ALPO-11 CATALYSTS - Gurjar, Shyamji; Thakur, Udaypal Singh; Tomar, Radha (International Journal of Current Pharmaceutical Research, 2015)
Crystalline AlPO-11 and its metal substituted CoAlPO-11 was prepared by the hydrothermal method and characterized by X-ray diffraction, scanning electron microscopy, Fourier transform infrared (FT-IR) spectroscopy and ICP-AAS. All the samples crystallized with the AFI structure. The catalytic properties of the catalysts in cyclodehydration of 1, 4-butandiole to THF. CoAPO-11 with more Lewis acid sites, and stronger Bronsted acid sites gave better activity than AlPO-11. Keywords: Metal substituted aluminophosphate molecular sieve, Butanol, THF.